Algebraic Operations-Based Secret-Key Design for Encryption Algorithm (ASKEA) for Energy Informatics and Smart Internet of Things (IoT) Applications - Al-Ghaili A.M.; Kasim H.; Omar R.; Hassan Z.; Al-Hada N.M.; Wang J. (Springer Science and Business Media Deutschland GmbH, 2023)
Algebra; Codes (symbols); Cryptography; Algebraic operations; Encryption algorithms; Energy informatics; Energy internet; Energy internet-of-thing; Key lengths; Plaintext; QR codes; Secret key; Security scheme; Internet of things